Preimplantation genetic diagnosis of alpha-thalassemia -SEA using novel multiplex fluorescent PCR - Piyamongkol W. (2014)
Purpose: Preimplantation genetic diagnosis (PGD) is an alternative to prenatal diagnosis (PND) giving couples at risk a chance to start a pregnancy with a disease-free baby. This study aimed to develop a new PGD protocol for alpha-thalassemia -SEA mutation, the commonest Mendelian disorder. Patients and methods: Multiplex fluorescent PCR was employed for mutation, contamination and linkage analysis. A couple experienced termination of pregnancy following positive PND decided to join the project. Results: Novel primers for alpha-thalassemia -SEA mutation amplifying 5 DNA fragments were developed. Two PGD cycles were performed, resulting in an un-affected baby. PND confirmed the heterozygous result. From 24 embryos, 87.5% of affected genotype were of best quality compared to 0% and 18.2% of those with normal and heterozygous, respectively. Conclusions: A novel PCR protocol for the common alpha-thalassemia -SEA mutation is reported. This test should be widely applicable. Interestingly, a potential effect of alpha-thalassemia -SEA mutation on preimplantation embryonic development was noticed. © 2011 Springer Science+Business Media, LLC.